PENINGKATAN MINAT BELAJAR PESERTA DIDIK DALAM PEMBELAJARAN SENI BUDAYA MELALUI MODEL PEMBELAJARAN KOOPERATIF MEANINGFUL INSTRUCTIONNAL DESIGN (MID) DI KELAS XI.IPA.2 SMAN 1 PASAMAN - Mistiawati, Mistiawati (Jurnal Manajemen Pendidikan, 2017)
Based on the learning process of students Class XI.IPA.2 SMAN 1 Pasaman in Cultural Arts learning found that the interest of learners in the learning of Art Culture is still very low. The purpose of this study is to describe and obtain information about the Improvement of Learning Interest of Learners in Cultural Arts Learning through Cooperative Learning Model Meaningful Instructionnal Design (MID) in Class XI.IPA.2 SMAN 1 Pasaman. This study is a classroom action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 31 students of Class XI.IPA.2 SMAN 1 Pasaman. The research data was collected by using observation sheet. Data were analyzed using percentages. Based on the results of the research and discussion that has been stated in the previous chapter, it can be concluded that it can be concluded that the Meaningful Instructionnal Design (MID) learning model can increase students' learning interest in Cultural Arts in SMAN 1 Pasaman. Learning interest of learners from cycle I to cycle II. Student learning interest in cycle I was 70.82 (enough) increased to 89.50 (good) with an increase of 18.68